MULHERES, TECNOLOGIAS E VIOLÊNCIAS DE GÊNERO: UMA REVISÃO BIBLIOGRÁFICA NARRATIVA - VIEIRA MOMBACH , VANESSA; DE MOURA BRACHTVOGEL , CATERINE; LAURA ARNHOLD , ANA; SIMONE VIONE SCHWENGBER , MARIA (Salão do Conhecimento, 2020)
REVISÃO BIBLIOGRÁFICA